(untitled) (Global Journal of Science Frontier Research, 2024)
South China Sea competition is real and hostile. Following the South China Sea Arbitration, the dynamics of territorial sovereignty in the South China Sea have shifted considerably. The position of ASEAN as the most enduring regional organization in the "global south" faces challenges, particularly in balancing rising great power competition in the Indo-Pacific region. ASEAN as a regional institution may be able to deal with some uncertainties, but it is impossible to overcome the recurrent "power dilemma," particularly when powerful states are intent on disrupting the existing quo. However, ASEAN must continue to act as an impartial arbiter in a strategic environment characterized by competing interests. ASEAN cohesion is very important and if the territorial issue is not properly managed, it might jeopardize regional stability and affect all member states. Without cohesiveness and centrality, existing ASEAN mechanisms and multilateralism can never be successful, and great powers will continue to intervene in the region’s affairs.